Surveillance in Maritime Scenario using Deep-Learning and Swarm Intelligence - Islam, Nazmul; Rahman Bhuiya, MD. Samiur; Drishty, Ayesha Siddiqua; Saha, Snigdha Suparna; Akash, Utsha Das (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.